Effects of deglaciation on Alpine stream ecosystems: preliminary findings - Brighenti, S.; Bruno, M. C.; Tolotti, M.; Wharton, G.; Bertoldi, W. (Universität Innsbruck, 2017)
Introduction: Climate change driven loss of cryosphere is determining radical shifts in stream hydrology and ecology in the European Alps. The key role of glaciers as a driver for Alpine freshwaters is decreasing, while rock-glaciers (permafrost) will likely become increasingly important due to their slower degradation rates. However, although interstitial ice degradation can have drastic effects on outflow chemistry (e.g. increased conductivity, acidification, and contamination by metals, and), very little is known on habitat and ecology of rock glacier-fed streams. Materials and methods: A set of glacier, rock-glacier and groundwater fed streams have been selected in the Zay and Solda catchments (South Tyrol, Italy). Channel stability (Pfankuch index), physical parameters (temperature, turbidity, suspended solids), water origin (H-O isotope analysis), chemistry (including conductivity, ions, nutrients, metal concentrations, and DOC), biofilm biomass (AFDM) and chlorophyll-a have been analysed at 12 sites in summer 2017 by monthly samplings. Results and discussion: Different stream types differ in their physical and chemical conditions. Longitudinal gradients and seasonal patterns can be identified as well, especially in glacier-fed streams. Rock glacier-fed streams can be considered as peculiar habitats, especially in the late summer when highest conductivity and metal concentrations have been observed. Characterization of biotic communities (diatoms, macroinvertebrates and meiofauna diversity and abundance) and foodweb analyses (C, N isotopes, metal uptake and transfer) are ongoing and, along with habitat characterization, will allow us to better understand the ecological shifts associated with deglaciation in the European Alps.